Preparation and Characterization of MUC-30-Loaded Polymeric Micelles against MCF-7 Cell Lines Using Molecular Docking Methods and in Vitro Study - Norased Nasongkla (2022)
MUC-30 is a hydrophobic compound which is active against the MCF-7 cancer cell line. In this study, MUC-30 was loaded in polymeric micelles to improve the water solubility and release rate. For prolonged MUC-30 release, MUC-30 was encapsulated in polymeric micelles using PEG-b-PLA and PEG-b-PCL as materials. Micelles prepared with 1: 9 w per w ratios by film hydration achieved the highest entrapment efficiency (EE%). The EE% of MUC-30-loaded PEG-b-PCL micelles was approximately 30% greater than that of PEG-b-PLA micelles, due to the different H-bond formations between MUC-30 and the polymer membrane (PCL, 4; PLA, 3). The cytotoxic activity of MUC-30 against EGFR theoretically presented 399.31 nM (IC50 = 282.26 ng/mL) by molecular docking. In vitro cytotoxic activity of MUC-30 was confirmed by MTT assay. MUC-30 (IC50 = 11 ± 0.39 ng/mL) showed three-fold higher activity over MUC-30-loaded PEG-b-PLA micelles (IC50 = 37 ± 1.18 ng/mL) and two-fold higher over PEG-b-PCL micelles (IC50 = 75 ± 3.97 ng/mL). This was due to the higher release rate of MUC-30 from PEG-b-PLA micelles compared to PEG-b-PCL micelles. Therefore, MUC-30-loaded PEG-b-PLA micelles could be a promising candidate for breast cancer chemotherapy.